Impact of Exopolysaccharides from Fructilactobacillus sanfranciscensis Ls5 on the Quality of Mantou: A Comparative Study of Fermentation Conditions - Juanxia Wang; Huiying Tian; Jiale Wang; Jingjing Liang; Jiao Li; Luciana Jimenez; Pascal Lejeune; Shiwei Zhou; Guohua Zhang (Foods)
Lactic acid bacteria (LAB) and their exopolysaccharides (EPS) have the potential to enhance the quality of flour-based products. This study investigated the effect of EPS produced by Fructilactobacillus sanfranciscensis Ls5 on the quality of Mantou. LAB strains with high EPS production were isolated from traditional fermenters, and their characteristics and EPS properties were examined. Four different fermentation conditions (Blank, Yeast, Ls5-Yeast, and EPS-Yeast) were compared in terms of their effects on the physicochemical properties, in vitro digestion characteristics, and shelf-life of Mantou. The incorporation of Ls5 and its EPS into Mantou resulted in a lower dough fermentation pH, increased organic acid production, and enhanced fermentation activity. Additionally, the incorporation of Ls5 and its EPS led to significant improvements in the quality of the Mantou, including the extension of shelf-life, improved sensory evaluation, and a reduction in the sugar content. Additionally, there was an increase in resistant starch content during digestion in both types of Mantou, which could offer potential benefits to human glycemic health.